Matters of Life and Death Perspectives on Public Health, Molecular Biology, Cancer, and the Prospects for the Human Race. - Cairns, John (Princeton University Press, 1997)
"John Cairns has made significant contributions to cancer research, molecular biology, and virology. He believes that it is possible to explain what is known about cancer and about molecular biology in terms that are easily understood by people with little or no scientific training. In this fascinating book he explores the revolution in public health, the origins and principles of molecular biology, and our emerging understanding of the causes of cancer. Finally, he discusses how these developments are likely to affect future generations."--Jacket.